KAJIAN PENGELOLAAN HUTAN MANGROVE DI KAWASAN PERLUASAN LAHAN KONSERVASI DESA KARANG REJO KOTA TARAKAN KALIMANTAN TIMUR - Wiharyanto, Dhimas (Jurnal Harpodon Borneo, 2011)
Mangrove are repositories of immense biological diversity and are also the nursery and breeding ground of several marine life forms, such as species of prawns, crabs, fishes and mollusks. For Rehabilitation and add of mangrove conservation area, Tarakan Government bought 12 ha of brackish water pond. The aims of this research are: 1) to description of mangrove forest and community in conservation area added, and 2) to formulate the management strategies capability of mangrove forest in Karang Rejo Village, Tarakan city, East Kalimantan. SWOT analysis used to take for certain management strategies of mangrove based on area potencies result. The dominant mangrove species in this area is Sonneratia alba and Avicennia alba. Community around of mangrove forest conservation agrees with conservation program. Management strategies priority for management are : 1) Action of the law, 2) monitoring and protection action, 3) Ecotourism mangrove development, 4) working together of all stakeholders in area of location, 5) human resources improvement, and 6) rehabilitation and add of mangrove species. Keywords : Mangrove, Management.